Bone Marrow Blood Vessels: Normal and Neoplastic Niche - Shahrabi, Saeid (Oncol Rev, 2016)
Blood vessels are among the most important factors in the transport of materials such as nutrients and oxygen. This study will review the role of blood vessels in normal bone marrow hematopoiesis as well as pathological conditions like leukemia and metastasis. Relevant literature was identified by a Pubmed search (1992-2016) of English-language papers using the terms bone marrow, leukemia, metastasis, and vessel. Given that blood vessels are conduits for the transfer of nutrients, they create a favorable situation for cancer cells and cause their growth and development. On the other hand, blood vessels protect leukemia cells against chemotherapy drugs. Finally, it may be concluded that the vessels are an important factor in the development of malignant diseases.